INVESTIGATING THE PROSPECT OF AUTONOMOUS TRAM (AT) TRANSIT CONSIDERING DAILY MOBILITY PATTERNS AND EXISTING BUS SERVICES COVERAGE IN SURAKARTA - Mohammad Bintang Lazuardi Rachmanie; Dyah Titisari Widyastuti; Alyas Abibawa Widita (Built Environment Studies, 2023)
Development of equitable and environmentally friendly public transit services is a pre-requisite if Indonesian cities were to attain sustainability objectives. Recent advances in transportation technology have introduced Autonomous Tram (AT) as an environmentally conscious option. This article investigates the prospect of implementing AT system using Surakarta as a case study. In doing so, we qualitative observe daily mobile patterns obtained through a primary survey and by considering existing Batik Solo Trans (BST) bus routes. Results indicate locations of road corridors most prominently used, overlapped with the existing bus services, indicating the geographic prospects of where to locate the AT system, The results from this study are expected to be a reference in AT research as a potentially sustainable public transportation service in Indonesia.